2019
DOI: 10.1136/oemed-2018-105331
|View full text |Cite
|
Sign up to set email alerts
|

Night work and sick leave during pregnancy: a national register-based within-worker cohort study

Abstract: ObjectiveThe aim of our study was to investigate the acute effect of night work during pregnancy on the risk of calling in sick the following day using register-based information and the workers as their own controls.MethodsUsing the payroll-based national Danish Working Hour Database, including all public hospital employees in Denmark, we identified 9799 pregnant women with ≥1 day shift and ≥1 night shift and ≥1 day of sick leave during the first 32 pregnancy weeks from January 2007 to December 2013. We perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 35 publications
(12 reference statements)
0
8
0
8
Order By: Relevance
“…However, our findings are in accordance with prior study showing the risk for sick leave in shift workers compared with scheduled workers. 12 Suga et al 30 previously reported that non-regular employees more frequently changed their occupations five times more than regular employees do; part-time and short-term contract employees were 12 times more likely to have occupation changes. Non-permanent workers have substantially more barriers to taking the frequent or sudden leaves of absence that are frequently required during infertility treatment while still being engaged in their jobs.…”
Section: Discussionmentioning
confidence: 98%
“…However, our findings are in accordance with prior study showing the risk for sick leave in shift workers compared with scheduled workers. 12 Suga et al 30 previously reported that non-regular employees more frequently changed their occupations five times more than regular employees do; part-time and short-term contract employees were 12 times more likely to have occupation changes. Non-permanent workers have substantially more barriers to taking the frequent or sudden leaves of absence that are frequently required during infertility treatment while still being engaged in their jobs.…”
Section: Discussionmentioning
confidence: 98%
“…In the same cohort, the risk of calling in sick within two days following night shifts was higher throughout pregnancy independent of individual factors and timeinvariant confounders (73), and -among night shift workers -the risk of hypertensive disorders of pregnancy, including pre-eclampsia, grew with increasing number of consecutive night shifts, particularly among obese women (body mass index ≥30 kg/m 2 ) (74). The results support that, in order to reduce risk of miscarriage, pregnant women should have no more than one night shift in a week (table 4).…”
Section: Duration Of Night Shiftsmentioning
confidence: 99%
“…Tras la lectura de título y resumen se evaluaron a texto completo 6 estudios, entre los cuales una revisión narrativa que, tras analizarla, quedó excluida debido a que incluía artículos no relacionados con el tema a estudio o estaban fuera del periodo de tiempo analizado (Figura 1). De los 5 artículos incluidos, 4 fueron observacionales de cohortes [18][19][20][21] y 1 fue una serie de casos 22 .…”
Section: Resultsunclassified